Extraversion Is a Mediator of Gelotophobia: A Study of Autism Spectrum Disorder and the Big Five - Tsai, Meng-Ning; Wu, Ching-Lin; Tseng, Lei-Pin; An, Chih-Pei; Chen, Hsueh-Chih (Frontiers in Psychology, 2018)
Previous research has shown that individuals with autism are frequently mocked in their childhood and are consequently more anxious about being ridiculed. Research has also shown that autistic individuals have a higher level of gelotophobia (fear of being laughed at) compared to typically developed individuals. However, recent studies have also found that gelotophobia is strongly related to personality, which suggests that personality is a factor that helps to create a higher level of gelotophobia in autistic individuals. To investigate whether this is the case, we recruited 279 Taiwanese high school students, 123 with autism spectrum disorder (ASD) and 156 typically developed students as a control group. Self-reporting questionnaires were used to gather data on the Big Five personality traits and on the gelotophobia-related traits of gelotophobia, gelotophilia, and katagelasticism. The results were analyzed and the two groups were compared for differences in gelotophobia and personality. The ASD group was found to have a higher level of gelotophobia than the typically developed group, but lower levels of gelotophilia and katagelasticism. Additionally, the ASD group was found to have lower levels of extraversion and agreeableness than the typically developed group, but no significant difference was found between the two groups in terms of conscientiousness, openness, and emotional stability. We then investigated the possible correlations between gelotophobia-related traits and the Big Five, and consequently the mediation effect of the Big Five on gelotophobia. The results show, firstly, that extraversion rather than ASD is a direct factor in gelotophobia. Secondly, the level of gelotophilia was partly influenced by autism but also to a certain extent by the level of extraversion. Lastly, the results indicate that autism and the level of agreeableness are in conflict when predicting the level of katagelasticism.